1984
DOI: 10.1080/00207548408942449
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the performance of pure and hybrid group technology manufacturing systems using computer simulation techniques

Abstract: comparative study of the performance of pure and hybrid group technology manufacturing systems using computer simulation techniques C. L. ANG and P. C. T. WILLEytProblems of workload imbalance in Group Technology (OT) can be mitigated by transferring workloads from a congested machine centre in one cell to an alternative, less congested machine centre in another cell. Such inter-cell workload transfer results in a GT system which is a hybrid between pure GT (in which components are completely processed within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 2 publications
0
45
0
Order By: Relevance
“…While such organization may be adequate when part families are clearly identifiable and demand volumes stable, they become inefficient in the presence of significant fluctuations in the demand of existing products or with the frequent introduction of new ones. A more detailed discussion of the limitations of cellular manufacturing systems can be found in [1,4,11,40,59,70,77]. These limitations resulted in recent calls for alternative cellular structures, such as overlapping cells [1,39], cells with machine sharing [11,70], and fractal cells [4,59,77].…”
Section: Current Practicementioning
confidence: 99%
“…While such organization may be adequate when part families are clearly identifiable and demand volumes stable, they become inefficient in the presence of significant fluctuations in the demand of existing products or with the frequent introduction of new ones. A more detailed discussion of the limitations of cellular manufacturing systems can be found in [1,4,11,40,59,70,77]. These limitations resulted in recent calls for alternative cellular structures, such as overlapping cells [1,39], cells with machine sharing [11,70], and fractal cells [4,59,77].…”
Section: Current Practicementioning
confidence: 99%
“…These limitations resulted in recent calls for alternative and more flexible cellular structures, such as overlapping cells [1], cells with machine sharing [2] [32], and virtual cellular manufacturing systems [8]. For highly volatile environments, certain authors have even suggested, as discussed earlier, a completely distributed layout, where copies of a given machine type are dispersed as much as possible throughout the shop floor [20] or the creation of multiple identical cells as in the fractal layout [21] [35].…”
Section: Introductionmentioning
confidence: 99%
“…While such organization may be adequate when part families are clearly identifiable and demand volumes are stable, they become inefficient in the presence of significant fluctuations in the demand of existing products or with the frequent introduction of new ones. A discussion of the limitations of cellular manufacturing systems can be found in [1], [2], [10], and [39].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the impact of sub-batch workload transfer on machine utilization in CM has been evaluated [15]. In another study, intercellular part transfer is proposed as an effective means of improving the efficiency of CM systems by directing the extra workloads from over-utilized machines to other cells [1]. Yet another approach to the problem of bottleneck machines is the development of alternative process plans and the rerouting of parts for increased scheduling flexibility [11].…”
Section: Introductionmentioning
confidence: 99%